2018
DOI: 10.1177/0300060518807335
|View full text |Cite
|
Sign up to set email alerts
|

Single-center analysis of patients with frontal fibrosing alopecia: evidence for hypothyroidism and a good quality of life

Abstract: Objective Frontal fibrosing alopecia (FFA) is an underestimated scarring alopecia. This study aimed to examine epidemiological information, as well as predilection sites, associated diseases, and responses to therapy of patients with FFA. We also aimed to determine whether the extent or duration of disease correlated with the quality of life (QoL). Methods Twelve outpatients with FFA for > 2 years were analyzed. The Erlanger atopic score and the Functional Assessment of Non-life-threatening Conditions (FANL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Yet, our study is the first study to examine such a relationship. 3,7,10,14 Furthermore, Starace et al showed that there is no relationship between the disease duration and disease severity. 10 To our knowledge, there are no previous studies regarding the relationship between disease severity and eyebrow involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, our study is the first study to examine such a relationship. 3,7,10,14 Furthermore, Starace et al showed that there is no relationship between the disease duration and disease severity. 10 To our knowledge, there are no previous studies regarding the relationship between disease severity and eyebrow involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar to our study, Valesky et al reported that the most commonly reported comorbid diseases were hypothyroidism and hypertension. 14,15 It was suggested to routinely workup of the thyroid hormone levels in patients who have FFA due to this common frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies that evaluated the impact of FFA used quantitative measures such as the Dermatology Life Quality Index and indicated only mild disease burden. 4,5 The aetiology of FFA is not well understood, and this was distressing to participants in our study. The amount of money participants in our cohort were willing to pay for a one-time cure was considerably greater than for other chronic dermatological conditions.…”
mentioning
confidence: 83%
“…While the etiology remains a mystery, a number of theories have been proposed. One study showed a strong correlation between the incidence of thyroid disease and FFA, particularly hypothyroidism 8 . A genome‐wide association study has revealed four genomic loci: 2p22.2, 6p21.1, 8q24.22, and 15q2.1.…”
Section: Figurementioning
confidence: 99%
“…One study showed a strong correlation between the incidence of thyroid disease and FFA, particularly hypothyroidism. 8 A genome-wide association study has revealed four genomic loci: 2p22.2, 6p21.1, 8q24.22, and 15q2.1. Within the 6p21.1 locus, fine mapping indicated that the association is driven by the HLA-B*07:02 allele.…”
mentioning
confidence: 99%